Adubação potássica e tratamento de sementes nas podridões do colmo em milho - Neuls, Cézar Augusto (2012)
The objective of the present study was to evaluate the effect of potassium and seed treatment of corn rot stalk disease. In experiment 1 and 2 were used five potassium doses (0, 40, 80, 120 and 160kg ha-1) in soils with levels of 190 and 120ppm of potassium respectively. In experiment 3, six doses of potassium (0, 65, 97.5, 130, 162.5, 195kg ha-1), but with levels of 40ppm in soil were tested. In experiment 4 was tested the potassium effect with seed treatment. The experimental design was a randomized complete blocks with four replications and plots of 21.0m2. The following corn hybrids were testes: Pioneer 30R50, NK Sprint and Agroeste 1560 respectively for experiment 1, 2, 3 and 4. Experiments were conducted according to corn technical recommendations. Grain yield, incidence of stalk rot were assessed. It was also determined the content of phenolic compounds. Data were submitted to analysis of variance using the F test, followed by the use of linear and nonlinear regression analysis. The following conclusions were taken: 1) potassium has effect on the incidence of CSR, only under conditions of low levels in the soil; 2) Seed inoculum is one way of introduction of CSR causal agent in areas not previously cultivated with corn; 3) potassium does increase phenolic acid concentration, given higher tolerance to corn stalk rot.